Living out Islam : voices of gay, lesbian, and transgender Muslims - Kugle, Scott Alan, 1969- (New York : NYU Press, 2013)
"Muhsin is one of the organizers of Al-Fitra Foundation, a South African support group for lesbian, transgender, and gay Muslims. Islam and homosexuality are seen by many as deeply incompatible. This, according to Muhsin, is why he had to act. "I realized that I'm not alone--these people are going through the very same things that I'm going through. But I've managed, because of my in-depth relationship with God, to reconcile the two. I was completely comfortable saying to the world that I'm gay and I'm Muslim. I wanted to help other people to get there. So that's how I became an activist." Living Out Islam documents the rarely-heard voices of Muslims who live in secular democratic countries and who are gay, lesbian, and transgender. It weaves original interviews with Muslim activists into a compelling composite picture which showcases the importance of the solidarity of support groups in the effort to change social relationships and achieve justice. This nascent movement is not about being "out" as opposed to being "in the closet." Rather, as the voices of these activists demonstrate, it is about finding ways to live out Islam with dignity and integrity, reconciling their sexuality and gender with their faith and reclaiming Islam as their own. Scott Siraj al-Haqq Kugle is Associate Professor in the Department of Middle East and South Asian Studies at Emory University. His previous books include Rebel between Spirit and Law: Ahmad Zarruq, Juridical Sainthood and Authority in Islam; Sufis and Saints' Bodies: Mysticism, Corporeality and Sacred Power in Islamic Culture; and Homosexuality in Islam: Critical Reflection on Gay, Lesbian, and Transgender Muslims"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Homosexuality -- Religious aspects -- Islam; RELIGION / General; SOCIAL SCIENCE / Gender Studies; RELIGION / Islam / General; Electronic books